2013
DOI: 10.5402/2013/191786
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Influence of Serum Magnesium Levels on Overall Mortality and Cardiovascular Outcomes in Patients with Advanced Chronic Kidney Disease

Abstract: Background. Low serum magnesium has been associated with an increased cardiovascular risk in the general population and in dialysis patients. Our aim was to analyze the influence of serum magnesium on overall mortality and cardiovascular outcomes in patients with advanced CKD not yet on dialysis. Methods. Seventy patients with CKD stages 4 and 5 were included. After a single measurement of s-magnesium, patients were followed a mean of 11 months. Primary end-point was death of any cause, and secondary end-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…It is uncertain whether lower serum magnesium is the cause of malnutrition or the consequences of it. Although some studies have suggested that a lower serum magnesium level was a significant and independent predictor of CV mortality among chronic hemodialysis patients, the results have been inconsistent [13,14] . We believe that lower serum magnesium may be the only manifestation of malnutrition, which is not the initiating factor and may not play an independent role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether lower serum magnesium is the cause of malnutrition or the consequences of it. Although some studies have suggested that a lower serum magnesium level was a significant and independent predictor of CV mortality among chronic hemodialysis patients, the results have been inconsistent [13,14] . We believe that lower serum magnesium may be the only manifestation of malnutrition, which is not the initiating factor and may not play an independent role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in 283 patients with CKD (eGFR 30–59, 15–29, and <15 (not on dialysis)) in, respectively, 101, 86, and 96 patients), that were included from the moment of first referral to a Turkish renal unit because of renal failure, did show a statistically significant inverse relation between serum magnesium and cardiovascular fatal and nonfatal events (adjusted HR 0.21 (0.10–0.46) per 0.411 mmol/L higher serum Mg) [ 36 ]. Another study did not find a statistically significant relation between serum magnesium concentration and all-cause mortality [ 37 ]. In this study, follow-up ended after occurrence of a nonfatal cardiovascular event and this approach may, thus, have missed subsequent events, including cardiovascular mortality and all-cause mortality, leading to bias in the analysis of all-cause mortality [ 37 ].…”
Section: Epidemiological Associations Between Magnesium and Mortalmentioning
confidence: 99%
“…Another study did not find a statistically significant relation between serum magnesium concentration and all-cause mortality [ 37 ]. In this study, follow-up ended after occurrence of a nonfatal cardiovascular event and this approach may, thus, have missed subsequent events, including cardiovascular mortality and all-cause mortality, leading to bias in the analysis of all-cause mortality [ 37 ]. Collectively, the epidemiological studies demonstrate an association between a low serum magnesium concentration and both all-cause and cardiovascular mortality.…”
Section: Epidemiological Associations Between Magnesium and Mortalmentioning
confidence: 99%
“…Although some studies have suggested that lower serum Mg is a significant and independent predictor of CVD mortality among chronic HD patients, the results have been inconsistent [19,20]. We think that lower serum Mg may be a manifestation of malnutrition, which is not the initiating factor and may not play an independent role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%